Peripheral T-Cell Lymphomas: A Review of Current Approaches and Hopes for the Future - Skarbnik, Alan P.; Burki, Meher; Pro, Barbara (Frontiers in Oncology, 2013)
Peripheral T-cell lymphomas comprise a heterogeneous group of NHLs, with different clinical and biological behaviors, but with a common denominator of poor overall prognosis and lack of potentially curable approaches outside of the realm of stem cell transplantation. Recent data have elicited renewed hope in the treatment of this disease. The authors review the standard of care in treating PTCL, as well as novel therapeutic modalities.